CuO Bionanocomposite with Enhanced Stability and Antibacterial Activity against Extended-Spectrum Beta-Lactamase Strains - Hina Qamar (MDPI AG, 2021)
Worldwide, bacterial resistance to beta-lactam antibiotics is the greatest challenge in public health care. To overcome the issue, metal-based nanoparticles were extensively used as an alternative to traditional antibiotics. However, their unstable nature limits their use. In the present study a very simple, environmentally friendly, one-pot synthesis method that avoids the use of organic solvents has been proposed to design stable, novel nanocomposites. Formulation was done by mixing biogenic copper oxide (CuO) nanomaterial with glycerol and phospholipids isolated from egg yolk in an appropriate ratio at optimum conditions. Characterization was done using dynamic light scattering DLS, Zeta potential, high performance liquid chromatography (HPLC), and transmission electron microscopy (TEM). Further, its antibacterial activity was evaluated against the extended-spectrum beta-lactamase strains based on zone of inhibition and minimal inhibitory concentration (MIC) indices. Results from this study have demonstrated the formulation of stable nanocomposites with a zeta potential of 34.9 mV. TEM results indicated clear dispersed particles with an average of 59.3 ± 5 nm size. Furthermore, HPLC analysis of the egg yolk extract exhibits the presence of phospholipids in the sample and has significance in terms of stability. The newly formed nanocomposite has momentous antibacterial activity with MIC 62.5 μg/mL. The results suggest that it could be a good candidate for drug delivery in terms of bactericidal therapeutic applications.